Who's been using my burial mound? Radiocarbon dating and isotopic tracing of human diet and mobility at the collective burial site, Le Tumulus des Sables, southwest France. (April 2019) - James, Hannah F.; Willmes, Malte; Boel, Ceridwen A.; Courtaud, Patrice; Chancerel, Antoine; Ciesielski, Elsa; Desideri, Jocelyne; Bridy, Audrey; Wood, Rachel; Moffat, Ian; Fallon, Stewart; McMorrow, Linda; et al.
Abstract: The burial mound of Le Tumulus des Sables, southwest France, contains archaeological artefacts spanning from the Neolithic to the Iron Age. Human remains have been found throughout the burial mound, however their highly fragmented state complicates the association between the burial mound structure and the archaeological material. Radiocarbon dating and isotopic analyses of human teeth have been used to investigate the chronology, diet and mobility of the occupants. Radiocarbon dating shows that the site was used for burials from the Neolithic to Iron Age, consistent with the range of archaeological artefacts recovered. δ 13 C and δ 15 N values (from dentine collagen) suggest a predominately terrestrial diet for the population, unchanging through time. 87 Sr/ 86 Sr (on enamel and dentine) and δ 18 O (on enamel) values are consistent with occupation of the surrounding region, with one individual having a δ 18 O value consistent with a childhood spent elsewhere, in a colder climate region. These results showcase the complex reuse of this burial mound by a mostly local population over a period of about 2000 years. Highlights: Radiocarbon dating shows use of this burial mound spanning 2000 years. Carbon and nitrogen isotope data shows a predominately terrestrial diet. Strontium and oxygen isotope data shows most individuals are local to the region. Reuse of the burial mound occurred.